The Corticospinal Tract: A Biomarker to Categorize Upper Limb Functional Potential in Unilateral Cerebral Palsy - Jaspers, Ellen; Byblow, Winston D.; Feys, Hilde; Wenderoth, Nicole (Frontiers in Pediatrics, 2016)
Children with unilateral cerebral palsy (CP) typically present with largely divergent upper limb sensorimotor deficits and individual differences in response to upper limb rehabilitation. This review summarizes how early brain damage can cause dramatic deviations from the normal anatomy of sensory and motor tracts, resulting in unique “wiring patterns” of the sensorimotor system in CP. Based on the existing literature we suggest that corticospinal tract (CST) anatomy and integrity constrains sensorimotor function of the upper limb and potentially also the response to treatment. However, it is not possible to infer CST (re)organization from clinical presentation alone and conventional biomarkers like time of the insult, location and extent of the lesion seem to have limited clinical utility. Here we propose a theoretical framework based on a detailed examination of the motor system using behavioral, neurophysiological and magnetic resonance imaging measures, akin to those used to predict potential for upper limb recovery of adults after stroke. This theoretical framework might prove useful because it provides testable hypotheses for future research with the goal to develop and validate a clinical assessment flowchart to categorize children with unilateral CP.